(untitled) (Research, Society and Development, 2025)
The present study aims to present an example of real costs associated with various procedures. The methodology used is mixed, with initial exploratory research that does not go into depth, opening a line of research that can count on other subsequent works, and including a brief descriptive case study of a qualitative nature associated with direct research source in public data from a website of procedure costs. The results emphasize the importance of implementing cost assessment tools to improve decision-making processes in hospital administration and the health system.